Early antibiotics use in young infants with invasive bacterial infection visiting emergency department, a single medical center's experience - Ying-Hsien Huang; Jia-Huei Yan; Kuang-Che Kuo; Wei-Ting Wu; Chih-Min Su; I-Min Chiu (Elsevier, 2020)
Background: The Surviving Sepsis Campaign (SSC) recommends that intravenous antimicrobials be administered within one hour to treat sepsis in both adult and pediatric patients. However, most studies on the timing of antibiotics have been based on adults so far. Therefore, the goal of this study was to clarify the clinical outcomes of the timing of antibiotics use in young infants diagnosed with invasive bacterial infections. Methods: We conducted this retrospective, cohort study at a single tertiary medical center during the period of 2007-2013 and included young infants visiting the PED diagnosed with an invasive bacterial infection. Early antibiotics use is defined as broad-spectrum intravenous antibiotics given within one hour of a patient's triage at PED. In this study, we have analyzed the factors associated with early antibiotics use and measured such primary outcomes as mortality, ICU admission, ventilation support, and length of hospital stay. Results: A total of 1231 visits of young infants with fever occurred during our study period, and we included 41 patients in our study; 29 of them were diagnosed with bacteremia and the remaining 12 with bacterial meningitis. Early antibiotics use was also associated with a shortened hospital stay (14 ± 8.5 vs. 24 ± 19.6; p = 0.043). However, no statistical differences were observed with regard to mortality, ICU admission, or ventilation support. Conclusion: Among young infants that visited the pediatric department with an invasive bacterial infection, early broad-spectrum antibiotics use was not associated with reduced mortality rate, ICU admission, or ventilator support. However, it may have advantages regarding hospital length of stay. Key Words: young infant, invasive bacterial infection, early antibiotics use, hospital length of stay